Nutritional and chemical composition of black velvet tamarind (Dialium guineense Willd) and its influence on animal production: A review - Ogbuewu Ifeanyichukwu Princewill; Modisaojang-Mojanaga Morwaledi Morategi Cornelia; Mokolopi Baitsholetsi Gloria; Mbajiorgu Christian Anayo (Open Agriculture, 2023)
The world population is expected to double by 2050, creating a greater demand for animal protein sources. This calls for an increase in the supply of animal-derived foods in order to avoid food scarcity in the future. Non-ruminants, which would have been a panacea to this increased demand for animal-derived foods, have suffered from the rising costs of feed ingredient world-wide. The increase in the prices of conventional feedstuffs have attracted the attention of researchers on the potentials of lesser-known tropical medicinal plants like Dialium guineense Willd (black velvet tamarind) as a feed resource for non-ruminants. The increase in prices of conventional feedstuffs have attracted the attention of researchers on the potentials of lesser-known tropical medicinal plants. One such lesser-known tropical plant that can be used in chicken and livestock production is black velvet tamarind. The plant is found in many parts of the world. It belongs to the family Fabaceae, has high forage yield, resistant to drought and insects, and does not require annual cultivation. The whole seed is moderate in crude protein and fibre but high in carbohydrates. The leaf, on the other hand, is low in carbohydrate, moderate in crude protein, and high in ash. D. guineense stem bark and fruit are excellent source of essential oils, and rich source of dietary fibre, minerals, and vitamins for monogastrics. The plant is endowed with beneficial phytochemicals such as alkaloids, tannins, phenols, flavonoids which may serve as natural alternatives to in-feed antibiotics. D. guineense has beneficial pharmacological effects including antioxidant and antimicrobial properties. The purpose of this study was to review the body of knowledge on the nutritional and chemical composition of D. guineense and its impact in animal production.